IJABE Guidelines for Authors - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
1 About IJABE 2 Criteria for Publication 3 Journal Manuscript Format 4 Pre-submission Enquiries 5 Submissions 6 Peer-Review & Editorial Process